2022
DOI: 10.3389/fenvs.2022.976211
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of sustainable logistics service providers in multinational supply chain cooperation: An integrated theory-based perspective

Abstract: In recent years, suppliers’ sustainability has been the primary source of conflict in multinational supply chains. How suppliers from developing nations may accomplish sustainable development and competitive advantage goals has become a tough issue inside the multinational supply chain, particularly in the agri-food cold chain. Using an integrated theory-based perspective, this paper analyzes how sustainable logistics service providers’ supply chain cooperation (MSCC) might drive the sustainable transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Key trends include circular economy interest and e-procurement adoption, especially in ISO 14001-certified organizations [ 34 ]. Sustainable logistics is crucial in multinational SC collaboration [ 35 ]. Industrial agroforestry represents an innovative sustainable value chain [ 16 , 36 ], and there is a focus on CSR and Innovation [ 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Key trends include circular economy interest and e-procurement adoption, especially in ISO 14001-certified organizations [ 34 ]. Sustainable logistics is crucial in multinational SC collaboration [ 35 ]. Industrial agroforestry represents an innovative sustainable value chain [ 16 , 36 ], and there is a focus on CSR and Innovation [ 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by [70] suggests that improving the cold-chain logistics system through use of intelligent methods. Furthermore, the studies of [71], [24], [72], [7], [73], and [74]. examined the challenges of logistics service providers in providing effective services to consumers and suggested that meeting regulatory requirements, demands, proactive compliance strategies, continuous training programs, and having effective communication with service stakeholders will alleviate these challenges.…”
Section: Challenges Faced By Logistics Service Providers In Nigeriamentioning
confidence: 99%
“…The competition models of supply chains have been studied in industries such as the healthcare industry (Singh & Parida, 2022), e-commerce industry (Febransyah & Camelia Goni, 2022), agriculture industry (Yan et al, 2019), and information technology industry (Nowicka, 2019). From the perspective of supply chain cooperation, some scholars have studied supply chain cooperation models from industries such as e-commerce (Wang et al, 2023;Su et al, 2022;Wang et al, 2021) and environmental industry (Jiang et al, 2021). Secondly, some scholars have studied model reconstruction from the perspective of supply chain competition coordination methods (Narayanan et al, 2005;Iyer, 1998;, and resource return rate from the perspective of supply chain cooperation performance (Woo & Suresh, 2022;Momeni & Bagheri, 2022;Chen & Su, 2021;Zhou & Zhu, 2021).…”
Section: Introductionmentioning
confidence: 99%